2011
DOI: 10.3892/ijo.2011.1112
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic impact of disseminated tumor cells and microRNA-17-92 cluster deregulation in gastrointestinal cancer

Abstract: Abstract. The presence of tumor cells in the bone marrow (BM) could be relevant to identifying high risk of disease progression and death in gastrointestinal cancer. However, the molecular profile associated with disseminated tumor cells (DTCs) homing to the BM has yet to be defined. MicroRNAs (miRNA) play key roles in cellular processes implicated in cancer. Thus, we investigated in 38 patients with colorectal, gastric or pancreatic cancer whether the presence of BM-DTCs is associated with a specific miRNA tu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(42 citation statements)
references
References 46 publications
(91 reference statements)
1
41
0
Order By: Relevance
“…For example, we excluded three studies [54][55][56] that they considered eligible, for reasons already given in our Additional file 2: Supplementary Results. Furthermore, only studies up to December 2013 were included and therefore two large studies were omitted [18,44].…”
Section: Discussionmentioning
confidence: 99%
“…For example, we excluded three studies [54][55][56] that they considered eligible, for reasons already given in our Additional file 2: Supplementary Results. Furthermore, only studies up to December 2013 were included and therefore two large studies were omitted [18,44].…”
Section: Discussionmentioning
confidence: 99%
“…Remarkably, after 12 months, the BM status had changed in a quarter of patients [103]. Another recent study identified an association of DTC presence with adverse prognosis of the curatively resected patients [104].…”
Section: Presence and Clinical Significance Of Ctcs In Pbmentioning
confidence: 97%
“…Among these clusters, miR-17-92 cluster has been studied in various cancers like colon cancer [51], breast cancer [52], gastrointestinal cancer [53], lung cancer [54], pancreatic cancer [55]. The miRNAs present in this cluster are located in chromosome 13 and are upregulated in SCC compared to normal.…”
Section: Differential Categorizationmentioning
confidence: 99%